KUNCI PINTU MENGGUNAKAN PASSWORD - , RIEDO PRADIKA PUTRA, Nur Sulistyawati, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Has been carried out of design a tool to lock a door room used the password. The purpose of building this device is to the security system of the room. This system used to security room awake. This instrument is divided into two parts, which is part of the hardware and software. Hardware keypad, consisting of a system of minimum mikrokontroler ATMega 168 as a series of benders the input and output, a series of LCD display the output using. The software made using program software arduino. Data from keypad that berisis knobs, break into mikrokontroler ATMega 168 already containing program. If the output data when it is appropriate program be kicked out the results on buzzer will give off the sound to be signaling that the result of the data input by keypad that ' s right or wrong, to LCD will appear a text that is the result of a program that is in mikrokontroler ATMega 168 and to motor servo going to rotate corresponding output of the program in mikrokontroler ATMega 168 to regulate how long his motorcycle servo this is going to rotate. The output of a system of locks a door room used the password results have been mentioned, according to a draft is a program. Of the data can be said of that system now that can work well.